Effects of PipX on NtcA‐dependent promoters and characterization of the cox3 promoter region in the heterocyst‐forming cyanobacterium Anabaena sp. PCC 7120. Issue 9 (28th March 2014) - Camargo, Sergio; Valladares, Ana; Forchhammer, Karl; Herrero, Antonia
Abstract : In Anabaena, the pipX gene is induced in the cells differentiating into heterocysts, being the PipX factor required for full expression of late heterocyst‐specific genes. Here we show that PipX has a positive effect on in vitro binding of the transcription factor NtcA to DNA, as well as on transcript production, in different NtcA‐dependent promoters. We found that the cox3 operon, encoding a heterocyst‐specific terminal respiratory oxidase, is expressed from three nitrogen‐regulated promoters to which NtcA binds. At the three sites, NtcA binding is potentiated by PipX. Thus, PipX has a direct effect on gene expression influencing the activity of NtcA. Abstract : The PipX factor has a positive effect on binding of the transcription factor NtcA to DNA. In Anabaena the cox3 operon is expressed in heterocysts from three N‐regulated promoters activated by NtcA and PipX. PipX is a transcriptional regulator influencing the activity of NtcA.